Social Inclusion For Persons With Disabilities Through Access To Employment In Indonesia - Nurhayati, Siti (Universitas Islam Indonesia, 2020)
The aim of this article is to identify the forms of legal protection provided by the government to fulfil the right to work for persons with disabilities in Indonesia, and to know the path to creating an inclusive work environment for persons with disabilities in Indonesia. This article is a normative study following legislative and a comparative approach. The results showed that the form of legal protection provided by the Indonesian government to persons with disabilities in fulfilling the right to work is set forth in Law Number 8 of 2016 concerning persons with disabilities as stipulated in article 45 - article 60. This form of legal protection covers the procedure of recruitment, acceptance, work preparing, work position, sustainability of work, and the development of a fair career consideration without discrimination. It is possible to realize an inclusive work environment for persons with disabilities in the workplace by fulfilling the principle of inclusion, which mandates awareness, accessibility, involvement, and support for persons with disabilitiesKeywords: Law; disability; employment; inclusionInklusi Sosial Bagi Penyandang Disabilitas Melalui Akses Pekerjaan Di IndonesiaAbstrakTujuan dari artikel ini adalah untuk mengidentifikasi bentuk-bentuk perlindungan hukum yang diberikan oleh pemerintah untuk memenuhi hak atas pekerjaan bagi penyandang disabilitas di Indonesia, dan mencari jalan untuk menciptakan lingkungan kerja yang inklusif bagi penyandang disabilitas di Indonesia. Artikel ini merupakan studi normatif dengan pendekatan legislatif dan komparatif. Hasil penelitian menunjukkan bahwa bentuk perlindungan hukum yang diberikan pemerintah Indonesia kepada penyandang disabilitas dalam pemenuhan hak atas pekerjaan diatur dalam Undang-Undang Nomor 8 Tahun 2016 tentang Penyandang Disabilitas sebagaimana diatur dalam pasal 45 sampai pasal 60. Bentuk perlindungan hukum ini perlindungan meliputi tata cara rekrutmen, penerimaan, penyiapan kerja, kedudukan kerja, kelangsungan pekerjaan, dan pengembangan pertimbangan karir yang adil tanpa diskriminasi. Lingkungan kerja yang inklusif bagi penyandang disabilitas dapat diwujudkan di tempat kerja dengan memenuhi prinsip inklusi yang mengamanatkan kesadaran, aksesibilitas, keterlibatan, dan dukungan bagi penyandang disabilitas.Kata kunci: Hukum; disabilitas; pekerjaan; penyertaan